Pengaruh Brand Ambassador dan Brand Awareness Terhadap Keputusan Pembelian Produk Kosmetik Wardah di Kota Samarinda - Nurpianti Nurpianti; Heni Rahayu Rahmawati (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of brand ambassadors and brand awareness on the purchase decisions of Wardah cosmetic products in Samarinda City. The increasingly competitive cosmetics industry requires companies to implement effective marketing strategies to enhance consumer interest and purchasing decisions. Brand ambassadors serve as brand representatives who can build trust, create a positive brand image, and establish emotional connections with consumers, while brand awareness plays an essential role in improving consumers' ability to recognize and recall a brand. This research employed a quantitative approach using a survey method involving consumers of Wardah cosmetic products in Samarinda City. Data were collected through questionnaires and analyzed using multiple linear regression to examine the influence of the independent variables on purchase decisions. The findings indicate that both brand ambassadors and brand awareness have a positive and significant effect on purchase decisions, both partially and simultaneously. Furthermore, brand awareness demonstrates a more dominant influence than brand ambassadors in shaping consumers' purchase decisions. These findings suggest that companies should select credible brand ambassadors with positive public images while continuously strengthening brand awareness through consistent marketing communication strategies to enhance consumer trust and increase purchase decisions for Wardah cosmetic products in Samarinda City.